Pemberdayaan Masyarakat Desa Dolat Rayat Melalui UMKM Donat Wortel sebagai Inovasi Olahan Pangan Lokal - Ahmed Charelsyah Lbs; Farah Ananda Lubis; Muhammad Faiz; Naufal Ramadhan; Yahfizham Yahfizham (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
The Real Work Lecture Program (KKN) in Dolat Rayat Village is motivated by the problem of the abundance of carrot crops that have not been optimally processed so that it risks reducing its economic value. Through this activity, the KKN team seeks to empower the community by introducing the innovation of Carrot Donut MSMEs as a form of processing value-added agricultural products. The main goal of this program is to improve the entrepreneurial skills of the community, especially housewives and youth, in order to be able to develop local processed food products that are competitive and highly competitive. The implementation method includes observation of village potential, analysis of community needs, deliberation with village officials, preparation of training modules, direct practice of making carrot donuts, as well as training in digital marketing strategies and attractive product packaging. The results of the activities showed high enthusiasm from the participants, improved skills in production and marketing, and the emergence of new business initiatives based on local potential. Overall, this program has succeeded in encouraging community economic independence, strengthening the entrepreneurial spirit of villages, and creating sustainable business opportunities from previously underutilized carrot agricultural products.